An introduction to Web Matrix : ASP.NET development for beginners - Hardy, Colin; Stobart, Simon, 1966-; ScienceDirect eBooks (Oxford : Butterworth-Heinemann, 2003)
The essential introduction to using Microsoft's Web Matrix tool for ASP.NET development.
Front Cover; An Introduction to Web Matrix: ASP.NET Development for Beginners; Copyright Page; Contents; Chapter 1. Introduction; Chapter 2. Installing the environment; Chapter 3. Introduction to the Web Matrix tool; Chapter 4. Finding your way around Web Matrix; Chapter 5. Basic HTML elements; Chapter 6. Interacting with the user using ASP.NET forms; Chapter 7. Validation of user input; Chapter 8. Introduction to VB.NET; Chapter 9. Further programming; Chapter 10. Installing and creating a database; Chapter 11. Interacting with the database using SQL.
Includes index.
Print version record.
Elsevier
Keywords: Active server pages; Microsoft .NET Framework; Active server pages; Microsoft .NET Framework; Web site development; Internet programming; REFERENCE -- General; Internet programming; Web site development; Electronic books